Description of Physical Activity Level of Medical Faculty Students of Pasundan University in The New Normal Era - Ajeng Annamayra; Ricky Septian Ramli; lutfi nur (Jurnal Maenpo : Jurnal Pendidikan Jasmani Kesehatan dan Rekreasi, 2022)
Physical activity has various benefits, especially for health because it can prevent degenerative diseases and other non-communicable diseases. The level of physical activity is also in line with the level of physical fitness and this is very important for students to be able to carry out good learning activities and ultimately affect the learning outcomes and achievements achieved. The existence of reports of cases of new sub-variant COVID infection indicates that the COVID-19 pandemic is not over and demands adaptation to new restrictions in daily activities that we know as the new normal. This also has an impact on the physical activity carried out by the community, especially students. The purpose of this study was to describe the physical activity of students in medical faculty at Pasundan University in the new normal era. Quantitative descriptive survey method was used in this study with A total of 149 students became participants.. The instrument used to measure physical activity is the International Physical Activity Questionnaire Short Form (IPAQ-SF). Descriptive analysis is used as an analytical technique in interpreting data. The results of this study showed that 68 students (45.7%) were included in the low physical activity category, then 64 students (42.9%) were in the medium physical activity category, and 17 students (11.4%) with high physical activity. The conclusion of this study is that the physical activity level of PSPD FK Unpas students in the new normal era as a whole is in the "low" category. These findings are expected to be used as evaluation material for students and institutions, considering that the level of physical activity is an important component related to health.Key words: physical activity level, medical students, new normal, IPAQ-SF